Sudden death: do cytokines and prothrombotic peptides contribute to the occurrence of ventricular fibrillation during acute myocardial infarction? - Elmas, Elif; Popp, Tatjana; Lang, Siegfried; Dempfle, Carl-Erik; Kälsch, Thorsten; Borggrefe, Martin (International journal of cardiology, 2010)
Aims - Sudden cardiac death (SCD) is frequently caused by ventricular fibrillation (VF) occurring in the course of acute myocardial infarction (AMI). It has not been investigated yet, to what extent markers of coagulation activation and inflammation differ between patients with and without VF in the acute phase of AMI.
Available online: 30 June 2009
Gesehen am 22.05.2023